Conception of clinical anthropology in medicine - N. A. Kornetov (Бюллетень сибирской медицины)
Historic retrospective of development of integral approach to medicine has been stated. Some result and systematization of multiple investigations on the problem «constitution and illness» has been summarized. New data has been introduced about absence of tropism of schizophrenia, peptic ulcer, cerebrovascular diseases to definite constitution type. In this association contemporary images about human constitution have been formulated. Theoretic bases of coming-to-be of integrative anthropology have been considered in native medicine and psychology; its sections have been distinguished. Definitions, principles and methods of clinical anthropology have been given and its value for medicine has been considered including medical education.